2006
DOI: 10.1096/fj.05-5618fje
|View full text |Cite
|
Sign up to set email alerts
|

p38 Kinase rescues failing myocardium after myocardial infarction: evidence for angiogenic and anti‐apoptotic mechanisms

Abstract: As a leading cause of heart failure, postinfarction left ventricular remodeling represents an important target for therapeutic interventions. Mitogen-activated protein kinases regulate critical cellular processes including stress response and survival, but their role in left ventricular remodeling is unknown. In the present study, rats were subjected to myocardial infarction by ligating the left anterior descending coronary artery. Western blot and kinase assay analysis revealed an inactivation of p38 kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…22 In our experimental setting, the rescue of p38 MAPK and p44/42 MAPK expression by C21 7 days after MI coincided with an improvement of cardiac function and a smaller scar size. Although this is an observation of coincidence, a causal relationship between MAPK activation and improved cardiac function is supported by a recent study by Tenhunen et al, 23 in which the authors were able to improve postinfarct cardiac function by rescuing p38 MAPK expression through local adenovirus-mediated p38 MAPK gene transfer. Functionally, MAPK rescue reduced fibrosis and apoptosis (the latter shown by terminal deoxynucleotidyl transferase dUTP nick end labeling staining and, as in our study, by a reduction of caspase-3).…”
Section: Discussionmentioning
confidence: 82%
“…22 In our experimental setting, the rescue of p38 MAPK and p44/42 MAPK expression by C21 7 days after MI coincided with an improvement of cardiac function and a smaller scar size. Although this is an observation of coincidence, a causal relationship between MAPK activation and improved cardiac function is supported by a recent study by Tenhunen et al, 23 in which the authors were able to improve postinfarct cardiac function by rescuing p38 MAPK expression through local adenovirus-mediated p38 MAPK gene transfer. Functionally, MAPK rescue reduced fibrosis and apoptosis (the latter shown by terminal deoxynucleotidyl transferase dUTP nick end labeling staining and, as in our study, by a reduction of caspase-3).…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that after myocardial infarction the activity of p38 falls, contributing to the development of apoptosis in the heart, increasing the downgrading of the function and the remodeling of the myocardial wall. When post-infarcted rats are treated with an adenoviral vector to overexpress p38, it prevents the deterioration of the myocardial function, has an anti-apoptotic effect, and avoids the fibrosis and remodeling of the ventricular wall (Bassi et al, 2008;Tenhunen et al, 2006).…”
Section: Apoptosismentioning
confidence: 99%
“…Among the molecular defects observed during HF, that have been explored as therapeutic targets, are the alterations in Ca 2+ handling during the excitation-contraction coupling (Hoshijima et al, 2002;Iwanaga et al, 2004;Kaprielian et al, 2002;Michele et al, 2004;Miyamoto et al, 2000;Most et al, 2004b;Most et al, 2007;Pleger et al, 2007;Pleger et al, 96 2005;Szatkowski et al, 2001), alterations in the -adrenergic receptors and their interaction with G proteins (Jones et al, 2004a;Koch, 2004;Maurice et al, 1999;Munch et al, 2005;Tevaearai et al, 2002), alterations of cellular signaling, including the members of the protein kinase C (PKC) family (Hambleton, 2006), and to the production of second messengers by the enzyme adenylyl cyclase (Lai et al, 2004). The apoptosis of cardiac myocytes also has been mentioned (Chatterjee et al, 2002;Tenhunen et al, 2006). Finally, the use of overexpressing angiogenic factors, also has been analyzed as alternatives in patients with HF secondary to ischemic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Rats were anesthetized with medetomidine hydrochloride and ketamine hydrochloride. The adenoviral construct (1 ϫ 10 9 infectious units in 100 L) was injected into the anterior wall of the left ventricle as previously reported (17 ). The animals were sacrificed 3 days after the gene transfer.…”
Section: Gene Transfermentioning
confidence: 99%